Fly-in fly-out: The challenges of transient populations in rural landscapes - McKenzie, Fiona Haslam (Springer, 2011)
Australia has experienced a prolonged economic boom and Western Australia in particular has benefited from the growing Indian and Chinese economies and their demand for mineral resources. The renewed mining fervour in Western Australia has had far reaching impacts in rural regions. Some communities are overwhelmed by a new population connected with mining, bringing with it a range of social and economic stresses and strains that small communities in particular, are struggling to cope with. In other communities, particular those in remote areas where housing and infrastructure are not able to meet the demands of burgeoning industry, fly-in fly-out (FIFO) labour forces increasingly underpin a wide variety of industry sectors. The scale of the FIFO work force is not easy to ascertain as the Australian Census does not specifically capture this information and the fluidity of the workforce makes it difficult for local authorities to calculate the working population and its demands. With such peripatetic populations, regional authorities struggle to maintain a sense of community and infrastructure without a rate-paying resident population, while local resources are stretched and often unable to cope with the increased FIFO population using them. This chapter will discuss the population changes that are occurring in rural, regional and remote Western Australia and the opportunities and challenges these changes present.